The Economic Cost of Stigma and the Exclusion of LGBT People : A Case Study of India - Badgett, M.V. Lee (World Bank, Washington, DC, 2015)
Human rights and equality for lesbian, gay, bisexual, and transgender (LGBT) people are usually considered through a social, cultural, or ethical lens, but equality and inclusion of LGBT people are also economic development issues. This report develops a model to estimate the economic cost of stigma; negative attitudes toward LGBT people and the exclusion of LGBT people in social institutions such as education, employment, families, and health care. The model is applied to a case study of India. Three major findings emerge from this report. First, there is clear evidence of stigma and exclusion exists for LGBT people in India. Data on public opinion from 2006 shows that 41 percent of Indians would not want a homosexual neighbor, and 64 percent believe that homosexuality is never justified. Negative attitudes have diminished over time, however. Second, the effects of stigma and exclusion are potentially costly to economies. A conceptual model links exclusion of LGBT people and economic development through (1) lower productivity and lower output as a result of employment discrimination and constraints on labor supply; (2) inefficient investment in human capital because of lower returns to education and discrimination in educational settings; (3) lost output as a result of health disparities that are linked to exclusion; and (4) social and health services required to address the effects of exclusion that might be better spent elsewhere. Third and lastly, in India, existing research does not allow for a precise estimate of the cost of LGBT exclusion, but the cost could be substantial. The loss of labor productivity and output because of employment discrimination and the loss of life years due to early death or disability will reduce the economic output of the Indian economy. With better research on the lived experiences of LGBT people, researchers could use existing analytical tools to estimate the total cost of LGBT exclusion.